Resilience Among Language Learners: The Roles of Support, Self-Efficacy, and Buoyancy - Li, Wenjiao (Frontiers in Psychology, 2022)
The growth of positive psychology has generated different perceptions and concepts on the authorization of learners, such as the construct of resilience and buoyancy. It has been argued that buoyancy has a central function in the educational process as buoyant pupils are more about to participate in activities presented in the classroom and also they are interested to cope with stress in challenging situations. Moreover, to protect against these adversities in reactions to unexpected situations, a related concept exists in positive psychology, labeled resilience that designates persistence and underlines people’s capabilities in face of adversities.The expansion of factors such as self-efficacy and social support seem to have great impacts on different aspects of learners. To this end, the present review attempts to highlight these two noteworthy elements in managing learners’ resilience and buoyancy. Consistent with this review, some recommendations for future inquiries are presented and instructional implications are offered.